2020
DOI: 10.3390/molecules25173820
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence as a Complementary Tool for UV-VIS Spectroscopy to Highlight the Photodegradation of Drugs: A Case Study on Melatonin

Abstract: In this work, a complementary ultraviolet-visible (UV-VIS) spectroscopy and photoluminescence (PL) study on melatonin (MEL) hydrolysis in the presence of alkaline aqueous solutions and the photodegradation of MEL is reported. The UV-VIS spectrum of MEL is characterized by an absorption band with a peak at 278 nm. This peak shifts to 272 nm simultaneously with an increase in the band absorbance at 329 nm in the presence of an NaOH solution. The isosbestic point localized at 308 nm indicates the generation of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Mel release behavior tests were carried out three times with a UV-Spectrophotometer (Shimadzu, JAPAN) at a wavelength of 220 nm at 37°C and standard solutions were prepared at 0.5, 1, 2, 5, and 10 mg/L, respectively. 30 To maintain the sink conditions, PBS was replaced with the same volume.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Mel release behavior tests were carried out three times with a UV-Spectrophotometer (Shimadzu, JAPAN) at a wavelength of 220 nm at 37°C and standard solutions were prepared at 0.5, 1, 2, 5, and 10 mg/L, respectively. 30 To maintain the sink conditions, PBS was replaced with the same volume.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Arguments for the formation of reaction compounds were often reported by Raman scattering and IR spectroscopy [ 35 , 36 , 37 , 38 ]. In order to exemplify this progress, the following issues were reported in previous studies by our team [ 35 , 36 , 37 , 38 ]: (1) the influence of oxygen from air on the photodegradation process of azathioprine in the powder and tablet state, respectively [ 38 ]; (2) the influence of the phosphate buffer (PB) solution with pH equal to 5.4 on photodegradation of folic acid [ 37 ]; and (3) the photodegradation induced by the hydrolysis reaction of melatonin [ 36 ] and acetaminophen [ 35 ]. In all these studies, PL was found to be a faster optical method in highlighting the photodegradation processes of the above drugs in comparison with the UV-VIS spectroscopy [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, for the drugs photodegradation monitoring, the optical methods often used were UV–VIS spectroscopy, XPS spectroscopy and photoluminescence (PL) 21 24 . Recently, using these three methods it has been demonstrated that: (1) azathioprine photodegrades in the presence of oxygen from air 21 ; (2) the photodegradation process of folic acid in phosphate buffer (PB) with pH equal to 5.4 is enhanced 22 ; and (3) melatonin and acetaminophen, respectively, also are susceptible for photodegradation in the presence of alkaline medium 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%